Nurses' perspective of work-related stressors. Issue 1 (March 2021) - Samuel, R; Zaini, N H; Hassan, W H W; Talib, A N; Ramly, F A
Abstract: There are many issues affecting the human resources in organizations today. The volatility in the global economy has brought about many changes and the human resources are the most affected. They have to learn to adapt to these changes and cope with the daily pressures. No industry is spared as change is seen as the only constant. This research attempts to ascertain stressors from the perception of nurses at a private hospital in Malaysia. It investigates issues pertaining to their workload, work environment, social support, and manpower. Random sampling determined the sample size from the population frame provided by the hospital's human resource department. Of the 108 nurses selected as respondents only 80 questionnaires were usable. The use of close-ended questionnaires using nominal and interval scales extracted information from the respondents. The data was then analyzed using the SmartPLS 3.3.2. Findings show that workload and manpower availability are stressors among the nurses. The management of the hospitals need to look into these two issues to help overcome the stress faced by the nurses.